Solution Processed Transparent Conductive Hybrid Thin Films Based on Silver Nanowires, Zinc Oxide and Graphene - ARAT, REFİK; Jia, Guobin; Dellith, Jan; Dellith, Andrea; Plentz, Jonathan (Elsevier, 2021)
Transparent conductive hybrid thin films based on silver nanowires (AgNW), zinc oxide (ZnO) and graphene were prepared using solution processing methods. For this study, the hexagonal (wurtzite) ZnO particles with a flower-like structure were synthesized by sol-gel reaction using zinc acetate dihydrate as a precursor at room temperature and pH value of 10. Ethanol dispersions of ZnO and commercial AgNW were deposited by spincoating method on glass substrates with fixed parameters to obtain AgNW-ZnO and ZnO-AgNW films, then their surfaces were covered with monolayer graphene flakes (MGFs) using a double self-assembly (DSA) process. The hybrid ZnO-AgNW-MGFs and AgNW-ZnO-MGFs films were characterized by XRD, SEM, UV?vis, four-point probe conductivity measurement, thermal (85 degrees C for 120 h) and long-term (ambient condition for 120 days) stability analyzes. The transmittances of AgNW-ZnO and ZnO-AgNW films were identical at 550 nm (80 %) and their sheet resistances (R-s) values were measured as 20.6 and 21.6 Omega/sq, respectively. After the MGFs deposition, the transmittances of hybrid films reduced to 72.5 and 76.8 %, while their R-s values decreased to 17.6 and 21.4 Omega/sq, respectively. Graphene flakes coating both enhanced the conductivity of hybrid films by improving the connection between silver nanowires and increased the thermal and long-term ambient stability of the films due to its barrier property against oxidation of silver nanowires.
Keywords: Transparent Conductive Electrodes; Silver Nanowires; Zinc Oxide Nanoparticles